З епістолярної фольклористики 1920—1930-х рр. О.Нікіфоров і українська фольклористика 1920—1930-х років ХХ ст. - Шевчук, Т.; Новійчук, В. (Народна творчість та етнографія, 2008)
Collecting and studying of the Russian fairy-tales were the matter of life of the famous Russian folklorist O. Nikiforov. Records of the Zaonezhzhya, Pinezhzhya and Mezen's folk-tales, done by the scientist during 1926–1928 years, prevail the known collection of O. Afanasyev after the amount of material. Greater part of the O. Nikiforov works remained unpublished, as well as most of his folk-lore records. The O. Nikiforov's correspondence to V. Petrov enriches a modern reader not only with new information concerning the field researches, that were carried out in 1920s – 1930 years but also the human measuring of the contacts of the Russian and Ukrainian scientists is exposed.